PERAN PENTING EKONOMI SYARI AH DALAM MENINGKATKAN TOLERANSI DAN PERDAMAIAN ANTAR UMAT BERAGAMA - Afifah Nur Aini; Tri utami Wulansari; Zhaza Faridahtunisa Kaluku; Dadan Mardani; Ali Aminulloh (STKIP Subang, 2025)
This study aims to examine the significant role of Islamic econ omics in promoting tolerance and fostering peace within multicultural and religiously diverse societies. In the context of increasing global interconnectedness, conflicts based on religion, ethnicity, and culture remain major challenges to social stability. Using a descriptive qualitative approach and literature study, this research analyzes the core principles of Islamic economics such as justice, equality, public interest (maslahah), and mutual cooperation and how these principles can be applied to create an inclusive and fair economic system. The findings reveal that Islamic economics, by emphasizing universal moral values and prohibiting exploitative practices such as riba (usury), maisir (gambling), and gharar (excessive uncertainty), fosters transparent and mutually beneficial economic relationships among people of different faiths. These principles not only contribute to economic well-being but also serve as a bridge for enhancing interfaith tolerance and social harmony. Consequently, Islamic economics stands as a strategic tool for building a peaceful and cohesive society. The study recommends broader implementation of Islamic economic values to strengthen social cohesion in Indonesia’s pluralistic context. Keywords: Islamic economics, tolerance, peace, justice, multiculturalism.